Intra Articular Hyaluronic Acid (Hylan G-F 20) in patients with knee meniscal injuries: A retrospective cohort study - Terence Babwah; Rohini Pattron; Crystal Adolph (Annals of Musculoskeletal Medicine - Peertechz Publications, 2017)
Aim: To determine the outcomes and satisfaction of patients who presented to a primary care musculoskeletal clinic and sports medicine clinic with a clinical or magnetic resonance imaging confirmation of knee meniscal tear and who subsequently received an injection of intra articular hyaluronic acid. Methods: This was a retrospective cohort study. Patients presenting to the clinics between January 2014 and July 2016 with an isolated diagnosis of knee meniscal tear and who subsequently received articular hyaluronic acid injection were selected. Evaluation of the pain was done using a numeric scale (0-10) before the injection and at least one year later. Duration of relief and patient satisfaction were also studied. Results: 103 of 156 eligible patients were selected (66%). Sixty three (61.2%) patients had relief of symptoms at least one year after the injection. Mean pain scales decreased from 8.03+/-1.36 at  reinjection moment to 3.34+/-2.58, 14.4+/-1.1 month after injection (p<0.005). Mean satisfaction with the procedure was 3.8+/-1.4 on a Likert Scale ranging from 1(very unsatisfi ed) to 5 (very satisfi ed). Eighty eight (85.4%) of patients would not consider surgical interventions as a first line treatment of their knee injury. Three patients (2.9%) eventually chose knee surgery. Conclusion: Intra articular hyaluronic acid injections for isolated knee meniscal tears in primary care patients provides relief of symptoms in the majority of cases and is well accepted by these patients. It is recommended as part of the initial treatment options.